Disrupsi AI terhadap Pembelajaran Agama Islam Tinjaun Filsafat Islam - Fitri Ekawati Mamonto; Selamat Rama Dani; Saiful Amri; Syamsul Arifin (Global Education Journal, 2026)
The development of Artificial Intelligence (AI) has brought major changes in the world of education, including in the learning of Islamic Religious Education (PAI). This study aims to examine the opportunities, challenges, and impacts of using AI in PAI learning based on the perspective of Islamic philosophy. The research uses the library research method by examining various books, scientific articles, and journals related to the research topic. The results of the study show that AI provides many benefits in learning, such as helping to tailor materials to the needs of students, providing chatbot-based learning assistants, monitoring learning progress, presenting more interesting learning simulations, and facilitating access to various sources of Islamic knowledge. Nonetheless, AI also has limitations because it only works based on data and algorithms. AI cannot replace the role of revelation, reason, spiritual values, or the process of forming students' morals. In the view of Islamic philosophy, teachers remain the main figures as murabbi, mu'allim, and mu'addib who guide, educate, and provide examples to students. Therefore, AI should be used as a learning tool that supports the application of Deep Learning through Meaningful Learning, Mindful Learning, and Joyful Learning, without ignoring Islamic values. Thus, the use of AI can improve the quality of learning while maintaining the main goal of Islamic education, which is to form knowledgeable, noble, and pious human beings.